The Ten Commandments: monuments of memory, belief, and interpretation - Hogue, Timothy S. (Cambridge University Press, 2023)
"Connects monumentality and material culture to questions of textual authority and literary history. It includes a comprehensive comparative study of the Decalogue (including new translation and analysis) and Levantine monuments that will be of interest to scholars of Hebrew Bible, Jewish studies, religious studies, archaeology, and art history"--